INDONESIAN DIPLOMACY TO SUPPORT DIGITAL TRANSFORMATION THROUGH THE 2022 G20 SUMMIT - Salsa Nabila Rifky; Nurfitri Nugrahaningsih; Dewi Suratiningsih (Jurnal Scientia, 2023)
The research aims to provide an explanation regarding how diplomacy is carried out by Indonesia to support digital transformation through the 2022 G20 Summit. This research entitled "Indonesian Diplomacy to Support Digital Transformation Through the 2022 G20 Summit" has an urgency related to digital issues facing Indonesia such as the need for adaptation habits are turning digital, digital infrastructure is not evenly distributed, digital security management and increasing unemployment. The research uses a descriptive qualitative research type with the literature study method. The research was analyzed using the theory of International Cooperation from Kalevi Jaakko Holsti. This theory explains that there are four stages related to international cooperation related to the issues studied, including: (1) The first stage, taking an approach by bringing solutions to problem solving, namely Indonesia in implementing the G20, making efforts to pay attention to infrastructure and services, regulations, cyber security and creating side event (2) The second stage, bargaining or discussing problems, namely Indonesia holding discussions in working groups at the G20 Summit such as the Working Group and Engagement Group, (3) The third stage, making conclusions to find out the truth, namely Indonesia through the Summit The G20 produces a Communique (an understanding taken from gathering facts) in discussions of the G20 groups (Working Group and Engagement Group), (4) The fourth stage, deciding on negotiations in an agreement or mutual understanding that satisfies all parties, namely Indonesia through the Summit The G20 produced a final understanding, namely the G20 Bali Leaders Declaration or Bali Declaration, which has 52 points of understanding and 5 of them discuss the issue of digital transformation.